Knowledge and Attitudes regarding Compliance with the Use of Personal Protective Equipment for Motor Vehicle Test Workers at the Malang Regency Transportation Service - Ani Asriani Basri; Fariz Zuvil Arganata; Nafilatul Fitri; Tiaravika Shafa Kamilah Vika (Universitas Muhammadiyah Malang, 2024)
The use of PPE is an effort to protect or prevent potential work hazards or accidents. Worker compliance in using PPE is determined by worker knowledge and attitudes. Workers' knowledge will change their actions so that this change in attitude will make workers obey the rules at work. The aim of this research is to analyze the relationship between knowledge and attitudes and compliance with the use of PPE among motor vehicle test officers at the Malang Regency Transportation Service. Quantitative analytical method, cross sectional approach. Total sampling was 30 respondents. Data was taken by filling out questionnaires by respondents and observing. Data analysis was carried out univariately and bivariately using the spss program with the Chi-Square statistical test. The Chi-Square test showed that there was a relationship between knowledge and compliance with the use of PPE (p-value = 0.043), and there was a relationship between attitude and compliance with the use of PPE (p-value= 0.027). The higher a person's level of knowledge and attitude, the more compliant they will be in using PPE.